ABCS OF NOT-FOR-PROFIT ACCOUNTING AND FINANCIAL /990 REPORTING - Scot, Laurence ([S.l.] : ROUTLEDGE, 2025)
Written in non-complicated prose and reducing complex rules to easily understandable concepts, this book offers a fundamental understanding of how not-for-profit (NFP) organizations are formed, their structure, and the unique accounting and reporting issues they face. In the United States, the NFP sector accounts for just over 10 percent of all private sector workers, and NFPs must comply with hundreds of rules imposed by the IRS, federal and state government agencies, foundations, and even donors. Yet there is a dearth of informative guidance, and a shortage of knowledgeable bookkeepers and accountants who understand the nuances of NFP accounting and financial reporting. Neither overly technical nor complex, this comprehensive and easy-to-read practical guide provides desperately needed information to a wide range of NFP stakeholders such as those who handle the bookkeeping and accounting functions, manage an NFP organization, provide funds or services to NFPs, or regulate NPF organizations. It covers topics such as the four required NFP financial statements, accounting for different types of revenue including conditional, restricted, and in-kind donations and sponsorships, IRS reporting on forms 990, 990-T and 990-PF, and how to understand and prepare for different types of audits. Including a glossary of important terms that are vital to running a successful NFP, and drawn from the author's decades of experience focused solely on the NFP sector, this is an indispensable guide for NFP leaders and staff, donors and grantors, regulatory agencies, consultants, accountants, bookkeepers, bankers, and any professionals whose work intersects the NFP sector.
Keywords: Nonprofit organizations -- Accounting; BUSINESS & ECONOMICS / Accounting / Financial